Y-Hf co-doped AlCoCrFeNi2.1 eutectic high-entropy alloy with excellent oxidation and spallation resistance under thermal cycling conditions at 1100 °C and 1200 °C. (15th July 2021) - Lu, Jie; Zhang, Han; Li, Ling; Chen, Ying; Liu, Xuanzhen; Zhao, Xiaofeng; Guo, Fangwei
Graphical abstract: Highlights: The oxidation rate of Y-Hf co-doped AlCoCrFeNi2.1 EHEA is much lower than that of NiCoCrAlYHf alloy. The Y-Hf co-doped AlCoCrFeNi2.1 EHEA exhibits a strong scale interfacial adhesion at 1100 °C and 1200 °C. The Y-Hf co-doped AlCoCrFeNi2.1 EHEA shows a highly structural stability after prolonged oxidation at 1100 °C and 1200 °C. The Y-Hf co-doped AlCoCrFeNi2.1 EHEA might be a promising candidate as the oxidation-protective overlay coating material. Abstract: The oxidation behavior of AlCoCrFeNi2.1 eutectic high-entropy alloy (EHEA) with Y-Hf co-doping under thermal cycling conditions at 1100 °C and 1200 °C is studied in comparison to the conventional NiCoCrAlYHf alloy (CNA). The oxidation rates of EHEA at two temperatures are much lower than those of CNA. Additionally, the resistance to Al2 O3 scale spallation for the EHEA is much superior to that for the CNA. It is well demonstrated that increasing the interfacial toughness is more beneficial to improve the scale spallation resistance in comparison to the decrease in oxidation rate.